RECODING EDUCATION. - Canta, Gerado (MEED Business Review, 2019)
The article discusses the efforts to provide coding education to primary school students in the United Arab Emirates (UAE) as of April 2019, highlighting the coding programme offered by management consulting firm Accenture. Topics include the need for young people to learn coding, the benefits of introducing children to coding in primary school, and the coding programmes in the UAE. Also explored are Accenture's programmes to encourage coding education worldwide.